Etika Komunikasi Islam di Media Sosial: Studi Kasus Penggunaan Bahasa dan Gaya Berkomunikasi Ustadz Abdul Somad - Erwan Efendi; Salman; Darul Arifin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze Islamic communication ethics applied by Ustadz Abdul Somad through case studies of his use of language and communication style on social media. The method used in this research is content analysis by examining various lectures and posts by Ustadz Abdul Somad on platforms such as YouTube, Instagram and Twitter. The main focus of this research is to explore how Ustadz Abdul Somad uses language that is polite, easy to understand, and in accordance with Islamic principles, as well as how he avoids hate speech, maintains politeness, and promotes constructive dialogue. The research results show that Ustadz Abdul Somad applies Islamic communication ethics which prioritizes openness, tolerance, honesty and trustworthiness in every message he conveys. The language used is simple but still full of meaning, and the communication style used prioritizes dialogue full of peace and respect, both between Muslims and with other parties. Thus, Ustadz Abdul Somad is an example of implementing Islamic communication ethics in the digital era, where technology and social media can be effective means for spreading da'wah wisely and responsibly.